Morphological and molecular data confirm the transfer of homostylous species in the typically distylous genus Galianthe (Rubiaceae), and the description of the new species Galianthe vasquezii from Peru and Colombia - Javier Elias Florentín; Andrea Alejandra Cabaña Fader; Roberto Manuel Salas; Steven Janssens; Steven Dessein; Elsa Leonor Cabral (PeerJ, 2017)
Galianthe (Rubiaceae) is a neotropical genus comprising 50 species divided into two subgenera, Galianthe subgen. Galianthe, with 39 species and Galianthe subgen. Ebelia, with 11 species. The diagnostic features of the genus are: usually erect habit with xylopodium, distylous flowers arranged in lax thyrsoid inflorescences, bifid stigmas, 2-carpellate and longitudinally dehiscent fruits, with dehiscent valves or indehiscent mericarps, plump seeds or complanate with a wing-like strophiole, and pollen with double reticulum, rarely with a simple reticulum. This study focused on two species that were originally described under Diodia due to the occurrence of fruits indehiscent mericarps: Diodia palustris and D. spicata. In the present study, classical taxonomy is combined with molecular analyses. As a result, we propose that both Diodia species belong to Galianthe subgen. Ebelia. The molecular position within Galianthe, based on ITS and ETS sequences, has been supported by the following morphological characters: thyrsoid, spiciform or cymoidal inflorescences, bifid stigmas, pollen grains with a double reticulum, and indehiscent mericarps. However, both species, unlike the remainder of the genus Galianthe, have homostylous flowers, so the presence of this type of flower significantly modifies the generic concept. In this framework, a third homostylous species, Galianthe vasquezii, from the Andean region is also described. Until now, this species remained cryptic under specimens of Galianthe palustris It differs however from the latter by having longer calyx lobes, the presence of dispersed trichomes inside the corolla lobes (vs. glabrous), fruits that are acropetally dehiscent (vs. basipetally dehiscent), and its Andean geographical distribution (vs. Paranaense). Additionally, a lectotype has been chosen for Diodia palustris, Borreria pterophora has been placed under synonymy of Galianthe palustris, and Galianthe boliviana is reported for the first time from Peru. A key of all Galianthe species with indehiscent mericarps is also provided.